Galectin-1 is associated with hematopoietic cell engraftment in murine MHC-mismatched allotransplantation - Shaikh, Ahmad; Gangaplara, Arunakumar; Kone, Abdoul; Almengo, Katherine; Kabore, Mariama D.; Ali, Mohamed A.E.; Xu, Xin; Saxena, Ankit; Lopez-Ocasio, Maria; McCoy, J. Philip; Fitzhugh, Courtney D. (Frontiers in Immunology, 2024)
Abstract Haploidentical hematopoietic cell transplantation (haplo-HCT) is associated with an increased risk of allograft rejection. Here, we employed a major histocompatibility complex (MHC)-mismatched allogeneic HCT (allo-HCT) murine model to better understand the role of Gal-1 in immune tolerance. Transplanted mice were classified into either rejected or engrafted based on donor chimerism levels. We noted significantly higher frequencies of CD4+ T cells, CD8+ T cells, natural killer cells, IFN- and TNF-producing CD4+ T cells, and IFN-γ producing dendritic cells and macrophages in rejected mice. Conversely, we found significantly increased frequencies of regulatory T cells (Tregs), predominantly Helios+, IL-10-producing CD4+ T cells, type 1 regulatory (Tr1) cells, and the proportion of Tr1+Gal-1+ cells in engrafted mice. Further, Gal-1 specific blockade in Tregs reduced suppression of effector T cells in engrafted mice. Lastly, effector T cells from engrafted mice were more prone to undergo apoptosis. Collectively, we have shown that Gal-1 may favor HSC engraftment in an MHC-mismatched murine model. Our results demonstrate that Gal-1-expressing Tregs, especially at earlier time points post-transplant, are associated with inducing immune tolerance and stable mixed chimerism after HCT.